2001
DOI: 10.1111/j.1553-2712.2001.tb01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Overcrowding Following Systematic Hospital Restructuring Trends at Twenty Hospitals over Ten Years

Abstract: Abstract. Objective: Hospital restructuring often results in fewer inpatient beds, increased ambulatory services, and closures of hospitals or emergency departments (EDs). The authors sought to determine the impact of systematic hospital restructuring on ED overcrowding. Methods: Time series analyses of average monthly overcrowding for EDs in Toronto, Ontario, Canada, from 1991 and 2000 (n = 20 hospitals, 120 months) were conducted. Autoregression models evaluated the rate of increase of overcrowding before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(99 citation statements)
references
References 18 publications
3
94
0
2
Order By: Relevance
“…As demand continues to increase for specialty services, such as ambulatory cancer care, 23 monitoring the ambulatory-emergent-inpatient feedback relationships will be essential when making decisions about hospital resource allocation. 24 We also observed that the proportion of GIM admissions that were repeat visits grew significantly during the study period. This may reflect overly aggressive discharge planning, lack of outpatient care coordination or deficits in the quality of care.…”
Section: Cjem • Jcmumentioning
confidence: 57%
“…As demand continues to increase for specialty services, such as ambulatory cancer care, 23 monitoring the ambulatory-emergent-inpatient feedback relationships will be essential when making decisions about hospital resource allocation. 24 We also observed that the proportion of GIM admissions that were repeat visits grew significantly during the study period. This may reflect overly aggressive discharge planning, lack of outpatient care coordination or deficits in the quality of care.…”
Section: Cjem • Jcmumentioning
confidence: 57%
“…The cost-effectiveness of vaccinating low-risk people remains controversial, [19][20][21][22][23][24][25][26][27][28][29][30] and although numerous studies have looked at the causes of ED utilization and overcrowding there are no data suggesting influenza causes overcrowding. [31][32][33][34][35][36] However, although universal vaccination may have little influence on ED volumes, vaccinating individuals at high risk for complications arising from influenza provides an average direct cost savings of $117 per person, in addition to reducing the number of hospitalizations and deaths.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Although the reasons and mechanisms are complex, 4,5 increasing volume and lack of inpatient beds are clearly major factors. [6][7][8] Conceptual models such as the input-throughputoutput model, 9 the Fields chaos model, 10 and the ED Cardiac Analogy Model 11 have been introduced in an effort to understand the factors of overcrowding and their mechanisms. Even the definition of overcrowding is problematic, 12 giving rise to various proposals for measuring ED crowding [13][14][15] and developing consensus on indices of overcrowding.…”
mentioning
confidence: 99%